An Actor-critic Algorithm Using Cross Evaluation of Value Functions - Hui Wang; Peng Zhang; Quan Liu (IAES International Journal of Robotics and Automation (IJRA), 2018)
In order to overcome the difficulty of learning a global optimal policy caused by maximization bias in a continuous space, an actor-critic algorithm for cross evaluation of double value function is proposed. Two independent value functions make the critique closer to the real value function. And the actor is guided by a crossover function to choose its optimal actions. Cross evaluation of value functions avoids the policy jitter phenomenon behaved by greedy optimization methods in continuous spaces. The algorithm is more robust than CACLA learning algorithm, and the experimental results show that our algorithm is smoother and the stability of policy is improved obviously under the condition that the computation remains almost unchanged.